The effect of oxidative modifications of amino acid residues in the active center of tyrosinase on the process of graying = Wpływ oksydacyjnych modyfikacji reszt aminokwasowych w centrum aktywnym tyrozynazy na proces siwienia - Cwynar, Anna; Olszewska-Słonina, Dorota; Pukownik, Ewelina (Journal of Education, Health and Sport, 2015)
Cwynar Anna, Olszewska-Słonina Dorota, Pukownik Ewelina. The effect of oxidative modifications of amino acid residues in the active center of tyrosinase on the process of graying = Wpływ oksydacyjnych modyfikacji reszt aminokwasowych w centrum aktywnym tyrozynazy na proces siwienia. Journal of Education, Health and Sport. 2015;5(9):102-108. ISSN 2391-8306. DOI10.5281/zenodo.30027 http://dx.doi.org/10.5281/zenodo.30027 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A102-108 https://pbn.nauka.gov.pl/works/616347 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.07.2015. Revised 24.08.2015. Accepted: 24.08.2015. THE EFFECT OF OXIDATIVE MODIFICATIONS OF AMINO ACID RESIDUES IN THE ACTIVE CENTER OF TYROSINASE ON THE PROCESS OF GRAYING WPŁYW OKSYDACYJNYCH MODYFIKACJI RESZT AMINOKWASOWYCH W CENTRUM AKTYWNYM TYROZYNAZY NA PROCES SIWIENIA Anna Cwynar1, Dorota Olszewska-Słonina1, Ewelina Pukownik2 1 Katedra i Zakład Patobiochemii i Chemii Klinicznej, Collegium Medicum w Bydgoszczy 2 Katedra Pediatrii, Hematologii i Onkologii, Collegium Medicum w Bydgoszczy Summary Reactive oxygen species (ROS) are molecules that form during physiological processes of cellular metabolism. Production of ROS in the organism is strictly controlled by the system of numerous anti-oxidative mechanisms. Insufficiency of defense systems and an increase in the level of free radicals leads to disturbances of the oxidative-antioxidative balance, and consequently, to generation of oxidative stress. Many observations indicate that the process which underlies graying is oxidative stress induced by hydrogen peroxide. Milimole concentrations of hydrogen peroxide (H2O2) are accumulated within gray hairs. Its presence inhibits transformation of tyrosine to melanin through the inactivation of the enzyme tyrosinase. The cause of an increase in H2O2 level is most probably a decrease in activity of catalase (CAT) responsible for its detoxication. This is a significant step forward, since the studies have indicated that another enzyme, called pseudocatalase, may prevent generation of gray hair. Scientists are working on obtaining effective inhibitors of the process of graying that could in the future serve as medicines preventing premature graying. Finding the mechanisms responsible for this process creates possibilities for developing new objectives for pharmacological therapy. The aim of this work is to present current reports concerning the problem of graying and a potential participation of oxidative stress in the course of this process. Streszczenie Reaktywne formy tlenu (RFT) są molekułami powstającymi podczas fizjologicznych procesów metabolizmu komórkowego. Produkcja RFT w organizmie podlega ścisłej kontroli przez system licznych mechanizmów antyoksydacyjnych. Niewydolność systemów obrony oraz wzrost poziomu wolnych rodników prowadzi do zaburzeń równowagi oksydacyjno-antyoksydacyjnej, a w konsekwencji do generacji stresu oksydacyjnego. Wiele obserwacji wykazuje, że procesem leżącym u podłoża siwienia jest stres oksydacyjny indukowany przez nadtlenek wodoru. W obrębie siwych włosów gromadzone są milimolowe stężenia nadtlenku wodoru (H2O2). Jego obecność hamuje przemianę tyrozyny w melaninę poprzez inaktywację enzymu tyrozynazy. Przyczyną wzrostu poziomu H2O2 jest najprawdopodobniej spadek aktywności katalazy (CAT) odpowiedzialnej za jego detoksykację. Jest to znaczący krok naprzód, ponieważ badania wykazały, że inny enzym, zwany pseudokatalazą, może zapobiec tworzeniu się siwych włosów. Naukowcy pracują nad uzyskaniem skutecznych inhibitorów procesu siwienia, mogących w przyszłości służyć jako leki zapobiegające przedwczesnemu siwieniu. Poznanie mechanizmów odpowiedzialnych za ten proces stwarza możliwości na opracowanie nowych celów dla terapii farmakologicznej. Celem prezentowanej pracy jest przedstawienie aktualnych doniesień na temat problemu siwienia i potencjalnego udziału stresu oksydacyjnego w przebiegu tego procesu. Keywords: catalase, hydrogen peroxide, melanogenesis, oxidative stress, tyrosinase. Słowa kluczowe: katalaza, nadtlenek wodoru, melanogeneza, stres oksydacyjny, tyrozynaza.